The significance of computer technologies in detecting plagiarism in scientific works - O. V. Pikhurets (Bulletin of Kharkiv National University of Internal Affairs)
The article analyses problematic issues regarding the importance of using computer technologies in detecting plagiarism in scientific works. It was determined that the problem of plagiarism in science is not only a matter of legislation, but a manifestation of disdain for scientific ethics and moral standards by the scientists themselves. The issue of academic plagiarism must be solved comprehensively and with joint efforts, by applying effective mechanisms to prevent plagiarism.